Sustainabilities in the resourceful North - Lempinen, Hanna; Tennberg, Monica; Pirnes, Susanna-Elisabet (Routledge, 2020)
The Arctic and its development have been discussed mostly from the point of view of natural resources and the implications of their extraction for local communities and indigenous peoples. In contrast, Arctic sustainability science has moved toward investigating the complexity of entanglements of resources, local life and social development, due to the increasing awareness of the difficulty of measuring societal development and the politicized nature of the concept of sustainable development as well as the critical role of social sciences in conceptualizing Arctic sustainability concerns. The chapter briefly introduces these conceptual and theoretical debates over social and cultural sustainabilities, and also gives an overview on the relationship between resources, development and social and cultural (un)sustainability. In addition, it outlines the structure of the book and introduces its Euro-Arctic case studies.